Urban ecotourism destination: Exploring the potential of Kota Kinabalu City, Sabah, Malaysia - Nattana Simon (2020)
Ecotourism concept which refers to tourism activities in natural, undisturbed ecosystem often misfits with urban environment, however not impossible. Although Sabah is well known for its ecotourism market, the urban ecotourism concept in Kota Kinabalu city has never been explored. Kota Kinabalu is an entry point to other ecotourism destinations in Sabah and is strategically located in the South East Asia region, offers potential to the tourism industry. Current ecotourism destinations in Sabah faced carrying capacity issues thus need to explore new destinations. This paper analyzed local Kota Kinabalu resident and tourist’ perception and value pertaining to the potential of Kota Kinabalu city as an urban ecotourism destination and how preservation of green spaces in cities supports sustainability. Their perception on the attractiveness of the ecosystem, conservation values and destination access were intercepted in this study. Kota Kinabalu city is found to have unique and world class natural attraction, suitable as ecotourism product. Tourist’ motivation and satisfaction towards Kota Kinabalu city were also gauged, adopting the Importance-Performance Analysis method. Findings showed that Kota Kinabalu is highly potential as an urban ecotourism destination, and study results could assist decision makers in the local tourism industry in making tourism development decisions. This study identified potential urban green spaces within 10km radius from the city centre as ecotourism destination based on the standard minimum size of an urban green space. The findings demonstrate the need to positively exploit various perceived importance and values from stakeholders, coupled with the existing environmental features to pursue urban ecotourism and how ecotourism within Kota Kinabalu city could be an effective approach to enhance or preserve natural green areas. This study resulted in some findings that assists decision making in developing tourism in the state of Sabah.